Kinerja Program Studi Administrasi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta - Layla, Sheffany Nur; Rugaiyah, Rugaiyah; Rahmawati, Desi (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
The improving of performance in educational institution is expected to produce a good output. Many things must be prepared and have good performance to achieve the quality institution. This study focuses on the evaluation of the implementation of the Standards and Procedures Accreditation of Undergraduate Studies at Higher Education level in Education Administration Studies Program Faculty of Education, Universita Negeri Jakarta. The scope of study is limited to the evaluation of the implementation of standards and procedures for accreditation. This study uses Discrepancy Evaluation Model (DEM) as model evaluation. It evaluates the gaps of program that is based on intermediate state which is expected in the plan with that generated in the implementation of the program. Evaluation of the gap is intended to determine the level of compatibility between the standards prescribed in the program with the actual appearance of the program. The data source is data of financing,insfrastructure, information system, research, community service and cooperation in year 2013-2015.s These results indicate that; (1) the performance component on financing aspects, the aspect of financing is not directly managed by the study program. (2) the existing components of the infrastructure shows the percentage of achievement in the category of good. (3) the component information system shows the percentage of achievement in the category of good. (4) component research, community service and cooperation shows the percentage in the category of pretty good achievement. Based on the acquisition of the four components of the above, the performance Educational Administration Faculty of Education UNJ aspects of financing, infrastructure, information systems, research, service and cooperation demonstrated has good category.